2020
DOI: 10.11646/zootaxa.4789.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology of myrmecophilous immature stages of European Microdon species (Diptera: Syrphidae): updated identification key and new diagnostic characters

Abstract: Hoverflies (Diptera: Syrphidae) of the genus Microdon Meigen have larvae that live in ant nests where they are predatory on ant larvae. Reflecting the exceptional challenges of this very specialized lifestyle, Microdon eggs, larvae and puparia are highly distinctive in their morphology. Detailed descriptions of these immature stages is, however, lacking for all but a very few species, and much of this has been limited through the sole use of light microscopes. Here, using Scanning Electron Microscopy (SEM), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…fuscipennis (Macquart) placed in ant colonies face a mortality rate of 90% or even more. Other laboratory breeding ended with the same mortality rates (Witek et al, 2012;Scarparo et al, 2017Scarparo et al, , 2020. Furthermore, it has been demonstrated that high inbreeding levels drastically reduce larval survival and egg-hatching rates, contributing to the local extinction of small populations (Saccheri et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fuscipennis (Macquart) placed in ant colonies face a mortality rate of 90% or even more. Other laboratory breeding ended with the same mortality rates (Witek et al, 2012;Scarparo et al, 2017Scarparo et al, , 2020. Furthermore, it has been demonstrated that high inbreeding levels drastically reduce larval survival and egg-hatching rates, contributing to the local extinction of small populations (Saccheri et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…mutabilis , based on its affiliation with a different host genus ( Myrmica instead of Formica ), and on the length of the prothoracic horns (respiratory organs emerging anterodorsally during the pupal stage) (Schönrogge et al ., 2002). Further morphological diagnostic characters to distinguish the immature stages of these two species have been recently described (Scarparo et al ., 2020). Microdon myrmicae is mostly found in association with Myrmica scabrinodis , although many other Myrmica species are known to be suitable hosts ( e.g ., My.…”
Section: Introductionmentioning
confidence: 99%